Rabeprazole and Domperidone Induced Hyperprolactinemia in a Patient with Type 2 Diabetes Mellitus, Hypothyroidism and Peptic Ulcer Disease: A Case Report - M, Kiran; Chakraborty, Ananya (Universitas Padjadjaran, Indonesia, 2024)
Drugs are a common cause of hyperprolactinemia. They are common in patients taking antipsychotics, antiemetics, opioids, antidepressants, prokinetics and proton pump inhibitors (PPI). Rabeprazole is a relatively newer PPI. Domperidone is a well-known prokinetic and antiemetic drug. There are few reports of hyperprolactinemia & galactorrhea with fixed drug combination (FDC) of rabeprazole (20 mg) and domperidone (30 mg). Here, we report a case of 39-year-old diabetic and hypothyroid female patient who was on the above FDC for peptic ulcer disease on and off for the last four years and developed hyperprolactinemia. She showed neither clinical signs of galactorrhea nor amenorrhea. On routine blood investigations, she had increased prolactin level. Radiological evaluation of brain was normal. The drug was stopped and repeat prolactin was normal within one week of withholding. A diagnosis of rabeprazole and domperidone induced hyperprolactinemia was reached based on clinical, laboratory judgement and causality assessment.